Inter-Budget Relations in the Context of Budgetary Decentralization in Ukraine - N. V. Koren (Статистика України, 2017)
Radical transformation processes in the economy, administrative reform and modernization of the public relations system entail the need for building adequate regulatory mechanisms to eliminate influences of negative factors, stabilize and sustain the development dynamics in the conditions of limited resources. The prolonged prevalence of situational analysis for purposes of administrative decisions making on budget-related issues prevented from effective setting and implementation of strategic objectives, which, once coordinated, would enhance the effectiveness of reforms in the budget system in the whole and the mechanism for interbudget relations in particular. Their high effectiveness is a key and complicated objective of public finance administration in a country. Solutions of problems related with stabilization of economic dynamics, overcoming of consequences of financial and economic crisis require advanced theoretical approaches to enhancing the effectiveness of inter-budget relations as an important component of budget control.